Accuracy of Frozen Section Analysis of Urethral and Ureteral Margins During Radical Cystectomy for Bladder Cancer: A Systematic Review and Diagnostic Meta-Analysis - Laukhtina, Ekaterina; Rajwa, Pawel; Mori, Keiichiro; Moschini, Marco; D'Andrea, David; Abufaraj, Mohammad; Soria, Francesco; Mari, Andrea; Krajewski, Wojciech; Albisinni, Simone; Teoh, Jeremy Yuen-Chun; Quhal, Fahad; et al. (European urology focus, 2022)
CONTEXT: The question of the ability of frozen section analysis (FSA) to accurately detect malignant pathology intraoperatively has been discussed for many decades. OBJECTIVE: We aimed to conduct a systematic review and meta-analysis assessing the diagnostic estimates of FSA of the urethral and ureteral margins in patients treated with radical cystectomy (RC) for bladder cancer (BCa). EVIDENCE ACQUISITION: The MEDLINE and EMBASE databases were searched in February 2021 for studies analyzing the association between FSA and the final urethral and ureteral margin status in patients treated with RC for BCa. The primary endpoint was the value of pathologic detection of urethral and ureteral malignant involvement with FSA during RC compared with the final margin status. We included studies that provided true positive, true negative, false positive, and false negative values for FSA, which allowed us to calculate the diagnostic estimates. EVIDENCE SYNTHESIS: Fourteen studies, comprising 8208 patients, were included in the quantitative synthesis. Forest plots revealed that the pooled sensitivity and specificity for FSA of urethral margins during RC were 0.83 (95% confidence interval [CI] 0.38-0.97) and 0.95 (95% CI 0.91-0.97), respectively. While for the FSA of ureteral margins, the pooled sensitivity and specificity were 0.77 (95% CI 0.67-0.84) and 0.97 (95% CI 0.95-0.98), respectively. Calculated diagnostic odds ratios indicated high FSA effectiveness, and patients with a positive urethral or ureteral margin at final pathology are over 100 times more likely to have positive FSA than patients without margin involvement at final pathology. Area under the curves of 96.6% and 96.7% were reached for FSA detection of urethral and ureteral tumor involvement, respectively. CONCLUSIONS: Intraoperative FSA demonstrated high diagnostic performance in detecting both urethral and ureteral malignant involvement at the time of RC for BCa. FSA of both urethral and ureteral margins during RC is accurate enough to be of great value in the routine management of BCa patients treated with RC. While its specificity was great to guide intraoperative decision-making, its sensitivity remains suboptimal yet. PATIENT SUMMARY: We believe that the frozen section analysis of both urethral and ureteral margins during radical cystectomy should be considered more often in urologic practice, until quality of life-based cost-effectiveness studies can identify patients within each institution who are unlikely to benefit from it.
Keywords: Radical cystectomy; Margins of Excision; Frozen section; Humans; ureter; resekční okraje; Quality of Life; zmrazené řezy; Urothelial carcinoma; Cystectomy; lidé; kvalita života; nádory močového měchýře; Frozen Sections; Accuracy; Bladder cancer; cystektomie; Urinary Bladder Neoplasms; Ureter